169 Adult brainstem glioma mimicking as a neuro-infectious process: case report and literature review. Issue 6 (27th May 2022) - Wu, Kit; Coulden, Amy; Mahmood, Amira; Kentley, Jonathan; Salam, Sharfaraz; Ghosh, Rhia; Reisz, Zita; Bodi, Istvan; Britton, Tom
Abstract : Background and Aim : Brainstem gliomas are rare, accounting for less than 2% of adult gliomas. They are difficult to diagnose and challenging to treat [Hu et al, 2016]. Here, we report a patient with an unusual clinical presentation of brainstem glioma, supported by radiological and histopathological findings. Clinical presentation: A 61-year old male retired diver presented with 2-month history of worsening occipital headache, described as a constant pressure worse on lying down with migrainous features of nausea and light-sensitivity, and intermittent episodes of double vision and poor balance. Neurological examination on admission was normal. He progressed to develop double vision, left-sided weakness and worsening swallowing and respiratory function. Investigations: Blood tests for infections and vasculopathy were negative. Two CSF samples taken showed high protein (1.7g and 3.25g respectively) with the first showing 100% lymphocytes and the latter 56% monocytes and 42% lymphocytes. There were no malignant cells on immunophenotyping. MRIs demonstrated progressive of ring-enhancing lesions in brainstem in keeping with inflammatory con- ditions. Biopsy was not possible due to the centrally-located lesions. Despite receiving wide spectrum antimicrobials, steroids and respiratory support, he died 2 months later. Autopsy of the brain showed a glioblastoma with brainstem infiltration and cystic necrosis in the pons. Summary: Gliomatosis pattern and leptomeningeal and nerve root spreading of brainstem glioblastoma can be misleading signs with neuro-infections as a differential. Early neurosurgical intervention may aid diagnosis. kitwu@doctors.org.uk